Epoxy/phenolic nanocomposite based adhesives: Non-isothermal cure kinetic study - Abbas Deriszadeh; Farhad Shahraki; Loghman Mostafa; Ali B.M. Ali; Davod Mohebbi-Kalhori; Soheil Salahshour; A. Alizad (Results in Engineering)
The curing behavior of an epoxy/phenolic-based system containing graphene oxide (GO), and rubber powder as a toughening agent has been studied using differential scanning calorimetry (DSC) under non-isothermal conditions at a temperature from 0 to 200 °C. So, to better dispersion of GO nanoplates in the resin media, the surface of the GOs was modified by 1,12-diaminododecane and subsequently aforementioned reaction was confirmed by Fourier transform infrared spectroscopy (FT-IR) and thermogravimetric techniques (TGA). DSC results show that rubber powders despite toughening properties prohibited resin-curing reactions. On the other hand, modified GO led to the promotion of curing reactions. The results of differential and integral isoconversional approaches indicated low activation energy for nanocomposite containing modified GO. Furthermore, thermal stability results reveal that the maximum decomposition temperature and char yield values of samples were increased gradually by the addition of GO and rubber powder to the system.